1982
DOI: 10.1021/j100220a007
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic production of hydrogen from water by a p- and n-type polycrystalline iron oxide assembly

Abstract: The photodissociation of water to produce hydrogen has been accomplished using light in the solar range of the electromagnetic spectrum and in the absence of any external potential at 300K. The catalyst for the reaction is a polycrystalline pin diode assembly made out of ~-and Si-doped iron oxide. In 0.1 ¥ Na2S04 solution (pH = 6) the device produces hydrogen catalytically with rates of 1-2 H2 molecules per site per minute and its power conversion effici~ncy is about 0.05%. Iron oxide containing minerals could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 0 publications
0
61
0
Order By: Relevance
“…As with TiO 2 and WO 3 , Fe 2 O 3 (particularly the a-modification) has been examined in single crystal form, as thin films prepared by CVD [237,239,255,270], pyrolytic conversion of iron [240], and spray pyrolysis [248,[250][251][252][253], or as sintered pellets from powders [241][242][243][244][245][246]. A variety of dopants have been deployed to modify the host [242-245, 247, 250-253] and remarkably, p-type semiconductor behavior has been reported [242,244,245,251] in addition to the more commonly occurring n-type material. The main handicap with Fe 2 O 3 is its rather poor electronic and charge transport characteristics regardless of the method of preparation of the material.…”
Section: Recent Work On Tio 2 On Photosplitting Of Water Ormentioning
confidence: 99%
“…As with TiO 2 and WO 3 , Fe 2 O 3 (particularly the a-modification) has been examined in single crystal form, as thin films prepared by CVD [237,239,255,270], pyrolytic conversion of iron [240], and spray pyrolysis [248,[250][251][252][253], or as sintered pellets from powders [241][242][243][244][245][246]. A variety of dopants have been deployed to modify the host [242-245, 247, 250-253] and remarkably, p-type semiconductor behavior has been reported [242,244,245,251] in addition to the more commonly occurring n-type material. The main handicap with Fe 2 O 3 is its rather poor electronic and charge transport characteristics regardless of the method of preparation of the material.…”
Section: Recent Work On Tio 2 On Photosplitting Of Water Ormentioning
confidence: 99%
“…After Morin [40] had first reported unintentionally Mgdoped Fe203 to be p-type after firing in oxygen, Gardner et al [42] have systematically studied the electrical properties of high-purity a-Fe2O3 deliberately doped with 0.01 to 2.0 at.% Mg. Also Somorjai et al [33,35] reported the preparation of p-type Fe2O3 by doping with MgO. Recently, the photogeneration of hydrogen from water was reported to occur in a shortcircuited polycrystalline p/n diode assembly comprising Mg-doped (p-type), and Si-doped (n-type) iron oxide, albeit with a low power-conversion efficiency of 0.05% [32 -371.…”
mentioning
confidence: 99%
“…In the early 1980s, the rate of hydrogen production, using a-Fe 2 O 3 as photoelectrode, was very low and rarely reported [27,29,98]. In 1987, Khader et al reported evolution of 380 mmol hydrogen in 400 h from photocatalytic water dissociation in visible light using a-Fe 2 O 3 .…”
Section: Efficiency and Hydrogen Productionmentioning
confidence: 99%